Evaluation of polyvinyl alcohol (PVA) loading in the PVA/titanium dioxide (TiO2) thin film coating on polyvinylidene fluoride (PVDF) membrane for the removal of textile dyes. (October 2020) - Sakarkar, Shruti; Muthukumaran, Shobha; Jegatheesan, Veeriah
Abstract: Polyvinylidene fluoride (PVDF) membrane was coated with polyvinyl alcohol (PVA)/titanium dioxide (TiO2 ) solution using dip-coating method. The effect of PVA loading (0–12 wt%) at a fixed TiO2 concentration (1 wt%) was investigated through physical and morphological characterization of the membranes. The experimental results showed that increasing the PVA content from 0 to 12 wt% in the coating solution increased the hydrophilicity and tensile strength as well as the young's modulus of the coated membranes. It also increased the thickness of the thin film coating which enhanced the removal of dyes but affected the permeate flux adversely. Larger the molecular weight of the dye, higher the rejection and lower the permeate flux obtained. The antifouling performance of the membrane was studied using Bovine Serum Albumin (BSA) solution and the fouling was measured using the irreversible fouling factor. The results indicated that the PVA/TiO2 coated PVDF membrane had lower irreversible fouling factors compared to plain PVDF membrane. The PVDF membrane with a thin film coating containing 3 wt% of PVA and 1 wt% of TiO2 showed high photocatalytic degradation for the three dyes studied under UV irradiation due to uniform dispersion of TiO2 nanoparticles over the membrane surface. Further, smaller the molecular weight of the dye, larger the photodegradation that was observed. Graphical abstract: Image 1 Highlights: PVA/TiO2 dip coating changed the hydrophobic PVDF membrane surface to hydrophilic. High PVA content increased the removal of dyes but decreased the permeate flux. The photocatalytic performance of TiO2 increased up to 3 wt% of PVA in the coating. PVA/TiO2 coating provided improved antifouling properties to the membrane. Ideal composition: 16 wt% PVDF membrane coated with PVA/TiO2 (3 and 1 wt%).